“Which of you shall we say doth love us most”: King Lear and the necessity of salt - Pannen, Imke (Academic Quarter | Akademisk kvarter, 2011)
"Which of you shall we say doth love us most" - King Lear and the necessity of salt by Imke Pannen is initiated by the idea that the motifs of parents' love for their children and children's love for their parents are common themes in various narratives of all mankind. According to Pannen, the idea of a parent demanding a declaration of his or her child's love is a less recurrent topic in literature, but it does figure in myths and fairy tales. In the article, the focus is on this theme in Shakespeare's tragedy King Lear and The Salt Prince.